Faktor yang Berhubungan dengan Kepatuhan Iuran BPJS Mandiri pada Pasien di Puskesmas Kapontori Buton - Wa Ode Muthya Yusrin; Irma Irma; Lade Albar Kalza (Awatara Publisher, 2026)
Compliance of Non-Wage Recipient Participants (PBPU) in paying contributions is a challenge for the sustainability of the National Health Insurance (JKN). At the Kapontori Community Health Center, the arrears rate reached 47.6%, which risks hampering service accessibility. This study aims to identify factors related to compliance in paying BPJS Mandiri contributions in the Kapontori Community Health Center working area, Buton Regency. This quantitative study used a cross-sectional analytical survey design, conducted from April 2–27, 2026. The study population was service users categorized as BPJS Mandiri participants, with a sample of 164 respondents using a total sampling technique. Primary data were collected through structured questionnaire interviews and then analyzed using the chi-square test (α = 0.05). The respondent compliance rate was 52.4% (compliant) and 47.6% (non-compliant). The majority of respondents were aged 21–30 years (30.5%), female (55.5%), chose class 3 care (89.6%), had a high school/senior high school education (51.8%), and were unemployed/housewives (36.6%). Bivariate analysis showed a significant relationship between income (p = 0.008) and motivation (p = 0.000) and contribution compliance. Conversely, knowledge (p = 0.740) and service quality (p = 0.118) did not show a significant relationship. The study concluded that there is a relationship between income and motivation and compliance with independent BPJS contributions among patients using health services in the Kapontori Community Health Center, Buton Regency.